Characterisation of the functional group properties of biodiesel and other fuel products - Nurhazirah, Binti Basir (Universiti Malaysia Sarawak, UNIMAS, 2013)
This study attempts to examine the functional groups of various fuel products including biodiesel, emulsified biodiesel (E-biodiesel), petrol and diesel. Biodiesel was prepared for the study from different feedstock by transesterification process in a ratio 1:2 of oil to methanol with 1% w/v of catalyst. E-biodiesel was prepared by further addition of water and surfactant to the biodiesel. Petrol and diesel are commercially available. The fuel products were analysed using Fourier Transform Infrared (FTIR). The transesterification process of biodiesel was confirmed by the presence of the peak at 1196 cm-1 showing the characteristic of CH3-O group. As the E-biodiesel was made from cooking oil, the IR spectrum shows similar pattern of spectra except for O-H band peak. Petrol and diesel are differentiable from biodiesel with petrol sample indicated weaker transmittance band at 1740 cm-1 whilst this band is absent in diesel. Additionally, the transmittance bands at lower frequencies, typically in the region of 1300-1000 cm-1 , are not found in diesel.